Studies on hydraulic pump characteristics through experiment and simulation in MATLAB Simscape - Kamarudin, Muhammad Nizam; Md. Rozali, Sahazati; Mohd Aras, Mohd Shahrieel; Hairi, Mohd Hendra; Abdullah, Lokman; Ismael Rizman, Zairi (ARQII Publication, 2024)
Hydraulic pumps are the heart of hydraulic systems that convert electrical energy into mechanical energy. As the behavior of a specific type of hydraulic pump must be identified to cater to the pump's limits and operating range, precise pump selection for particular applications is a must. Hence, this paper presents the research findings on the characteristics of hydraulic pumps, focusing on pump parameters such as pump power, flow rate, and operating pressure. These parameters were evaluated under no-load operating conditions without actuators. The simulation setup is realized through Simscape on the MATLAB platform. The laboratory test rig exploits the advantages of Bosch Rexroth hydraulic pumps and other hydraulic components manufactured by the Rexroth group of companies. The findings from this research find a relationship between pump power, pressure, and flow rate. The simulation and experimental results showed good agreement with a very slight percentage difference, where the factors that contribute to the slight tolerance are thoroughly elaborated.